In-vitro antifungal susceptibility testing of lanoconazole and luliconazole against Aspergillus flavus as an important agent of invasive aspergillosis. Issue 2 (February 2019) - Omran, Saeed Mahdavi; Taghizadeh-Armaki, Mojtaba; Zarrinfar, Hossein; Hedayati, Mohammad T.; Abastabar, Mahdi; Moqarabzadeh, Vahid; Ansari, Saham; Saber, Sasan; Hoseinnejad, Akbar; Miri, Ali; Verweij, Paul E.; Seyedmousavi, Seyedmojtaba
Abstract: Introduction: The incidence of Aspergillus infections has recently increased remarkably in certain tropical and sub-tropical countries, with Aspergillus flavus being identified as the leading cause of infections after A. fumigatus. Lanoconazole (LAN) and luliconazole (LUL) are currently approved for topical treatment of cutaneous fungal infections. We aimed the in-vitro antifungal susceptibility testing of two imidazole, LAN and LUL against A . flavus. Methods: One hundred and eighty-seven clinical and environmental A. flavus were tested originating from different climate zones of Iran between 2008 and 2015. The identification of all isolates was confirmed by using PCR-sequencing of β-tubuline ribosomal DNA gene. In-vitro antifungal susceptibility test was performed using CLSI guidelines against LAN, LUL, itraconazole (ITC), voriconazole (VRC), posaconazole (POS), Isavuconazole (ISA), amphotericin B (AMB), 5-flucytosine (5FC), caspofungin (CAS) and anidulafungin (AFG). The minimum inhibitory concentration (MIC) and minimum effect concentration (MEC) values were evaluated according to CLSI M38-A2 guidelines. Results: The geometric mean MICs for tested antifungals, in increasing order, were: 0.009 μg/mL for LUL (ranging from 0.004 to 0.062), 0.02 μg/mL for LAN (ranging from 0.004 to 0.125), POS (0.10), ISA (0.16), ITC (0.24), VRC (0.27), AMB (1.8) and 5FC (63.06) μg/mL. The mean value of MECs for AFG and CAS were 0.06 and 0.07, respectively. Conclusion: Overall, LUL and LAN showed the lowest MIC against all isolates of A. flavus . Further studies are required to evaluate the in-vivo efficacy of these agents, and the possibility of using these agents in systemic infections.